Development of 3D printed gastroretentive floating tablet devices for metronidazole - Gundran, Althea C.; Bautista-Palacpac, Jocelyn S. (Manila : Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2022)
Gastroretentive drug delivery systems (GRDDs) remain buoyant in the stomach without being affected by the gastric emptying for a prolonged period. In this study, 3D-printed GRDDs shall enclose Metronidazole, a drug which locally acts in the stomach to eradicate Helicobacter pylori from causing peptic ulcer. The 3D printed devices are developed through Fused Deposition Modeling (FDM). This study used Quality by Design (QbD) with risk assessment and 2 factorial methods in order to ensure its quality development despite its novelty. There are four floating tablet devices custom-designed and prepared from Polyvinyl alcohol (PVA) filament. Density of all devices were less than 1.004 g/cm3, thus successfully exhibiting floatation. The Floating Lag time (FLT) showed instant floatation and Total Floating Time (TFT) lasted for an average of 1 hour. In vitro drug release kinetics exhibit Korsmeyer-Peppas kinetics showing prolonged drug release. Surface morphology showed consistent layers for tablet device 3. Their melting temperatures fall within 186.12 "C-187.27C, deemed acceptable. 3D CT X-ray results also show accuracy of printing 3D renders. Tablet device 3 exhibited the smoothest surface, longest floating time and slowest drug release. Plots from Design Expert Software results show the significant design models. Thus, that the devices exhibit prolonged drug release and are a promising design for further optimization studies. Keywords: Gastro-retentive drug delivery systems (GRDDS), Quality by Design (QbD), 3D printing, FDM printing, Factorial Method, Metronidazole Cytochrome P45O ABSTRACT enzyme-mediated herb-drug interactions may pose considerable risk for critical clinical consequences when co-administered with prescribed medications. Oral hypoglycemic agents such as sulfonylureas, meglitinides, and thiazolidinediones are substrates of the most abundant CYP2C subfamily in the human liver CYP2C9. Concomitant intake with herbal preparations which contain phytoconstituents that may potentially modulate drug metabolism could alter plasma drug concentrations, degree of drug efficacy and toxicity. Chamaecostus cuspidatus leaves traditional and commercial herbal preparations have been taken for diabetes mellitus in Southeast Asia with reports on combined use with allopathic medicine. The investigation of the risk of possible fatal outcomes such severe hypoglycemia through initial in vitro assessment of potential CYP2C9 inhibition by natural products may be of great importance for treatment optimization. The study assessed the ability of traditionally and commercially prepared Chamaecostus cuspidatus aqueous extracts to interfere with CYP2C9 activity via fluorescence-based enzyme assay. Among the aqueous extracts of Chamaecostus cuspidatus leaves, only the lyophilized leaf juice from Bacolod showed potential CYP2C9 inhibition. Flavonoids and alkaloids were detected via TLC and phytochemical screening which are the most likely class of metabolites in Chamaecostus cuspidatus responsible for the CYP2C9 inhibitory activity. Although none of the decoctions and tea preparations showed significant CYP2C9 percentage inhibition, further evidence is needed to determine the effect of heating on the CYP2C9-inhibiting compounds from Chamaecostus cuspidatus. injection volume, 3Ominute run time, Standard Solution using Rhein Reference standard (20mcg-2.5mcg/mL), Sample Solution of 1g of dried methanol extract in 100mL methanol. The resulting chromatogram shows the peak of the standard rhein at a Retention time of 5.101 minutes. Conclusion Standardization of 10 samples yielded limits to ensure that the identity, safety, and quality of Cassia fistula L. leaves are kept. Limits were set as follows, Total Ash not more than 10%, Acid Insoluble Ash not more than 2%, Water Soluble Ash not more than 3%, Loss on Drying and Moisture Content less than 10%, Water Soluble Extractives, not less than 12%, and Ethanol Soluble Extractives not less than 6%. For Microbial testing and Heavy metal testing, all samples must pass the requirements according to the set requirements under AO172 s 2004 of the Philippine FDA. For Identity, Thin Layer Chromatogram must be identical to the Chromatogram presented while for HPLC, a detection of Rhein at RT 5.101 using the HPLC Conditions.
Thesis (Bachelor of Science in Pharmaceutical Sciences)--University of the Philippines Manila, August 2022
Keywords: Metronidazole -- Dosage; Metronidazole -- Gastrosericus -- Drug delivery systems. -- Philippines .